(untitled) (Research, Society and Development, 2025)
This study aimed to analyze the main barriers faced by transgender people in accessing Primary Health Care (PHC). It is an integrative literature review, conducted through a search in the Virtual Health Library (VHL) between February and June 2025, using controlled descriptors, the PICo strategy, and the PRISMA protocol for study selection. A total of 62 articles were identified, of which 10 met the inclusion criteria and composed the corpus of analysis. The results identified eight main barriers that hinder transgender people’s access to PHC services, including the incorrect use of the social name, fear of discrimination, self-medication without professional supervision, lack of adequate structures, shortage of trained professionals, failures in the implementation of public policies, and significant impacts on the mental health of this population. It was observed that the lack of professional preparation, combined with the absence of specific training on gender diversity, exacerbates social and institutional exclusion. Moreover, the concentration of specialized services in large urban centers makes access difficult, especially for those living in peripheral regions. It is concluded that it is urgent to strengthen public policies, promote ongoing training for health professionals, and adopt welcoming practices and active listening to ensure comprehensive, humane, and discrimination-free care, contributing to the construction of a more equitable and inclusive Unified Health System (SUS).